Bartók György kézirata, mint Ravasz László forrása - SZETEY, Szabolcs (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2017)
Bartók György’s Manuscript as Ravasz László’s Source. The most influential homiletical book of the later reformed bishop, Ravasz László (The Theory of the Congregational Preaching Ministry – Homiletics, Pápa, 1915) had and has been respected and adapted by many scholars and ministers for more than one century since its publication. In the theological research, all sources of Ravasz’ book have not yet been clearly identified and clarified. A manuscript, mainly written in 1895/1896 by Bartók György (1845–1907), Ravasz’s later father in law and deputy professor of theology in Nagyenyed, coincides with more parts of Ravasz László’s book in several cases concerning the history of preaching in the Christian Church and in the Hungarian Reformed Church. The manuscript, described and analysed in this study, shows also the working method of the young professor Ravasz. The results of this paper contribute to the revaluation of the epochal work of Ravasz László and to the research of history of homiletics and preaching.